Gerakan Literasi Sekolah dalam Upaya Meningkatkan Minat Baca Siswa MIM PK Kertonatan Kartasura - Hanifah Fitriyani; Markhamah Markhamah (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
The literacy movement is a movement in an effort to improve abilities and insights in reading, writing, and so on so that learning can be created in everyday life. This study aims to describe the school literacy movement implemented by the school and identify the obstacles it faces. In this study using descriptive qualitative research type. This research technique was carried out by collecting data from various sources, namely teachers and students. This data collection was carried out using field observation techniques, documentation, and interviews followed by note taking techniques. The data analyzed consisted of data collection then described and a conclusion was drawn. From these conclusions it can be explained that MIM PK Kertonatan Kartasura is working hard to increase students' interest in reading, one of which is by implementing the 15-minute reading literacy movement. With this reading literacy movement, students will feel closer to literacy and books. In addition to the 15-minute reading literacy movement, MIM PK Kertonatan Kartasura also has a literacy movement such as reading the Koran, reading Iqro' and muroja'ah hadiths and short letters. Keywords: Literacy movement and interest in reading